청소년의 아동기 가정폭력경험이 데이트 폭력에 미치는 영향: 스트레스 대처의 조절효과를 중심으로 - 이병도; Byung Do Lee; 조춘범; Choon Bum Cho (청소년복지연구, 2013)
본 연구는 청소년의 아동기 가정폭력경험이 데이트 폭력에 미치는 영향과 두 변인의 관계에있어서 스트레스 대처의 조절효과를 검증하는데 연구목적이 있다. 이를 위해 경기 남·서부 지역을 중심으로 중·고등학교에 재학 중인 청소년 803명을 조사하여 이성교제를 경험했거나 교제 중인 청소년 568명을 분석하였다. 연구결과 청소년의 데이트 폭력 발생비율은 35.7%로 나타났다. 청소년의 아동기 가정폭력경험은 80.5%로 나타났다. 연구문제 검증 결과 청소년의 아동기가정폭력경험이 데이트 폭력에 영향을 주었다. 그리고 스트레스대처는 아동기 가정폭력경험과 데이트 폭력관계에서 조절효과가 검증 되었고, 스트레스대처 유형 중 사회적지지추구대처가 조절효과가 있는 것으로 검증 되었다. 이러한 연구결과를 토대로 청소년의 데이트 폭력에 대한 사회복지적 접근을 강화할 뿐만 아니라 원인인 가정폭력경험에 대한 접근도 함께 제시하였다. 또한 스트레스 대처와 대처 유형 중 사회적지지추구대처의 유형에 대한 개입방법도 함께 제시하였다. The purpose of this study is to identify the influence of family violence experiences of child on dating violence of middle-high school students, and to find out the moderating effects of stress coping. To obtain this purpose, subject was middle-high school students from GyungGi-DO areas and data collected was analyzed by SPSS 12.0. The major findings in this are the following. First, dating violence was about 35.7 percent and family violence experience of child was 80.5 percent. Second, dating violence is affected by family violence experiences of child. Third, stress coping showed to moderate the influence of dating violence affected by family violence experiences of child and in the stress coping, social support stress coping showed to moderate the influence of dating violence affected by family violence experiences of child. Based on the findings, the implications in terms of the field of social work are the following: first, the result of family violence experiences influence dating violence suggests that preventive interventions be applied to children who have experienced family violence directly or indirectly. Second, as stress coping and social support coping also suggests.